Metabolic biomarkers for predicting cardiovascular disease - Montgomery, Jana E (Dove Medical Press, 2013)
Cardiac and peripheral vascular biomarkers are increasingly becoming targets of both research and clinical practice. As of 2008, cardiovascular-related medical care accounts for greater than 20% of all the economic costs of illness in the United States. In the age of burgeoning financial pressures on the entire health care system, never has it been more important to try to understand who is at risk for cardiovascular disease in order to prevent new events. In this paper, we will discuss the cost of cardiovascular disease to society, clarify the definition of and need for biomarkers, offer an example of a current biomarker, namely high-sensitivity C-reactive protein, and finally examine the approval process for utilizing these in clinical practice.